WATER BLOWN POLYURETHANE SPRAY FOAM SYSTEM - ANDERSON, RAY, J; SPARKS, THOMAS, A; HARKINS, PHILIP, D (2006)
A composition and a method for producing primarily water blown polyurethane foams is provided. The composition uses isocyanate ratios greater than conventional foam system to provide a water blown polyurethane foam suitable for a wide variety of applications including spray roofing, insulation, etc. The preferred composition for preparing a polyurethane foam comprises an isocyanate component and a polyol component, wherein the polyol component preferably comprises a combination of Mannich polyol, polyester polyol, and polyether polyol. Preferably, the composition includes water to act as a blowing agent and a metal salt catalyst to assist in the reaction. Preferably, the isocyanate index is between about 1.2 and about 2.0. Additional catalysts, surfactants, flame retardants, and blowing agents may also be used depending upon the desired finished product. La présente invention concerne une composition et un procédé de production principalement de mousses de polyuréthane gonflées à l'eau. La composition utilise des proportions d'isocyanates supérieurs aux systèmes de mousse conventionnels servant à produire des mousses de polyuréthane gonflées à l'eau et convenant à une large gamme d'applications telles que les traitements de toitures et l'isolation. La composition préférée est essentiellement à base d'isocyanate et de polyol, ce dernier étant de préférence une association de polyol Mannich, de polyol de polyester et de polyol de polyéther. La composition comporte de préférence de l'eau servant d'agent gonflant et un catalyseur à sel métallique pour faciliter la réaction. L'indice d'isocyanate se situe de préférence entre environ 1.2 et 2.0. Suivant le produit fini voulu, on peut également utiliser d'autres catalyseurs, tensioactifs, ignifugeants et agents gonflants.